Origin of high Mg and SO 4 fluids in sediments of the Terceira Rift, Azores – indications for caminite dissolution in a waning hydrothermal system - Schmidt, Christopher; Hensen, Christian; Wallmann, Klaus; Liebetrau, Volker; Tatzel, M.; Schurr, S. L.; Kutterolf, Steffen; Haffert, Laura; Geilert, Sonja; Hübscher, C.; Lebas, Elodie; Heuser, Alexander; et al. (Geochemistry, Geophysics, Geosystems, 2019)
During R/V Meteor cruise 141/1, pore fluids of near surface sediments were investigated to find indications for hydrothermal activity in the Terceira Rift (TR), a hyper‐slow spreading center in the Central North Atlantic Ocean. To date, submarine hydrothermal fluid venting in the TR has only been reported for the D. João de Castro seamount, which presently seems to be inactive. Pore fluids sampled close to a volcanic cone at 2800 m water depth show an anomalous composition with Mg, SO4, and total alkalinity (TA) concentrations significantly higher than seawater and a nearby reference core. The most straightforward way of interpreting these deviations is the dissolution of the hydrothermally formed mineral caminite (MgSO4 0.25Mg(OH)2 0.2H2O). This interpretation is corroborated by a thorough investigation of fluid isotope systems (δ26Mg, δ30Si, δ34S, δ44/42Ca, and 87Sr/86Sr). Caminite is known from mineral assemblages with anhydrite, and forms in hydrothermal recharge zones only under specific conditions such as high fluid temperatures and in altered oceanic crust, which are conditions generally met at the TR. We hypothesize that caminite was formed during hydrothermal activity and is now dissolving during the waning state of the hydrothermal system, so that caminite mineralization is shifted out of its stability zone. Ongoing fluid circulation through the basement is transporting the geochemical signal via slow advection towards the seafloor.